Chalcogen Bonding: An Overview. Issue 7 (4th December 2018) - Vogel, Lukas; Wonner, Patrick; Huber, Stefan M.
Abstract: In the last few decades, "unusual" noncovalent interactions like anion‐π and halogen bonding have emerged as interesting alternatives to the ubiquitous hydrogen bonding in many research areas. This is also true, to a somewhat lesser extent, for chalcogen bonding, the noncovalent interaction involving Lewis acidic chalcogen centers. Herein, we aim to provide an overview on the use of chalcogen bonding in crystal engineering and in solution, with a focus on the recent developments concerning intermolecular chalcogen bonding in solution‐phase applications. In the solid phase, chalcogen bonding has been used for the construction of nano‐sized structures and the self‐assembly of sophisticated self‐complementary arrays. In solution, until very recently applications mostly focused on intramolecular interactions which stabilized the conformation of intermediates or reagents. In the last few years, intermolecular chalcogen bonding has increasingly also been exploited in solution, most notably in anion recognition and transport as well as in organic synthesis and organocatalysis. Abstract : Building bridges : Chalcogen bonds are noncovalent interactions similar to hydrogen bonds that are based on electrophilic chalcogen substituents. This Minireview provides an overview on the origin and features of chalcogen bonding as well as its applications in the solid state and in solution. A certain focus will be on the latter and particularly on the recent introduction of chalcogen bonding in noncovalent organocatalysis. LB=Lewis base.